Effects of Sr-doping on the giant magnetocaloric effect of EuTiO3. Issue 2 (1st February 2017) - Mo, Zhao-Jun; Sun, Qi-Lie; Wang, Chang-Hong; Wu, Hai-Zhen; Li, Lan; Meng, Feng-Bin; Tang, Cheng-Chun; Zhao, Yun; Shen, Jun
Abstract: The magnetic properties and magnetocaloric effect of Eu1−x Srx TiO3 ( x =0–0.1) compounds are investigated. With slight Sr-doping, the ferromagnetic (FM) coupling significantly increased and FM exchange is dominant in the delicate balance. A giant reversible magnetocaloric effect (MCE) and large refrigerant capacity (RC) for Eu1−x Srx TiO3 compounds were observed. The values of −Δ S M max are evaluated to be around 10 J/kg K under a magnetic field change of 1 T and 21 J/kg K under a magnetic field change of 2 T, respectively. But, the values of RC are increased with the more Eu in EuTiO3 to be substituted by Sr. Therefore, the giant reversible MCE and large RC make the Eu1−x Srx TiO3 compound a good candidate for magnetic refrigerant working at low-temperature and low-field.